2001
DOI: 10.1093/emboj/20.6.1394
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of RNA editing substrates facilitated by guide RNA-binding protein gBP21

Abstract: RNA editing within the mitochondria of African trypanosomes is characterized by the insertion and deletion of uridylate residues into otherwise incomplete primary transcripts. The reaction takes place in a high molecular mass ribonucleoprotein (RNP) complex of uncertain composition. Furthermore, factors that interact with the RNP complex during the reaction are by and large unknown. Here we present evidence for an editing-related biochemical activity of the gRNA-binding protein gBP21. Using recombinant gBP21 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
139
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(147 citation statements)
references
References 45 publications
6
139
2
Order By: Relevance
“…However, the Kd values were significantly lower for both the native and the reconstructed complexes, indicating a higher affinity of binding of the complex than either of the component proteins. The Kd for the binding of Ltp28 with single-stranded RNA was approximately 10-fold higher than that reported for the binding of T. brucei gBP21 to single-stranded RNA (Muller et al 2001), which may reflect a species variation or differences in the recombinant protein preparation. However, the Kd of binding of the Ltp26/Ltp28 complex to single-stranded RNA (9.6 nM) is nearly identical to that of gBP21 (Muller et al 2001).…”
Section: Rna-binding Properties Of the Purified And Reconstituted Ltpcontrasting
confidence: 54%
See 2 more Smart Citations
“…However, the Kd values were significantly lower for both the native and the reconstructed complexes, indicating a higher affinity of binding of the complex than either of the component proteins. The Kd for the binding of Ltp28 with single-stranded RNA was approximately 10-fold higher than that reported for the binding of T. brucei gBP21 to single-stranded RNA (Muller et al 2001), which may reflect a species variation or differences in the recombinant protein preparation. However, the Kd of binding of the Ltp26/Ltp28 complex to single-stranded RNA (9.6 nM) is nearly identical to that of gBP21 (Muller et al 2001).…”
Section: Rna-binding Properties Of the Purified And Reconstituted Ltpcontrasting
confidence: 54%
“…The RNA-binding mitochondrial protein gBP21, from T. brucei, has been extensively studied (Köller et al 1994;Allen et al 1998;Lambert et al 1999;Muller et al 2001) and has several properties that make it a very likely candidate for indirect involvement in editing. These involve high-affinity binding to gRNA and coimmunoprecipitation with in vitro editing activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that RNA editing of developmentally regulated transcripts requires the participation of specific protein factors that allow efficient gRNA/mRNA annealing. A number of gRNA binding proteins have been characterized that accelerate the hybridization of cognate guide RNA/pre-edited mRNA pairs [43][44][45][46]. Recently, Pelletier and Read [46] showed that RNAi knockdowns of the Y-box protein, RBP16, led to a 98% reduction in the levels of edited CYb mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial RNA-binding protein complex contains two small RNA-binding proteins and three associated proteins, and may possibly be involved in the initial annealing of the guide RNA and the mRNA (4)(5)(6)(7)(8)(9). The RNAediting terminal uridylyl transferase 1 (TUTase 1) (RET1) complex contains the RET1 tetramer and one or more unidentified components (10).…”
mentioning
confidence: 99%